Blackbirds Turdus merula as competent reservoirs for Borrelia turdi and Borrelia valaisiana in Portugal: evidence from a xenodiagnostic experiment - Norte, A.C. (2013)
To confirm that thrushes, such as blackbirds Turdus merula, play a role as reservoir for some Borrelia genospecies, we performed a xenodiagnostic experiment with blackbirds captured in a mixed wood located in Western Portugal where Borrelia turdi, an uncommon genospecies in Europe, was the most prevalent genospecies associated with birds. Two out of five birds harboured B. turdi infected Ixodes frontalis at the time of capture. Four out of five birds transmitted spirochaetes to Ixodes ricinus xenodiagnostic ticks: two birds transmitted Borrelia valaisiana to 25.7% and 10.5% of ticks, and two transmitted B. turdi to 6.4% and 5.4% of ticks. Our results showed that blackbirds transmit B. valaisiana and B. turdi to I. ricinus feeding larvae, acting as reservoir hosts for these genospecies in nature.